2012
DOI: 10.5152/tud.2012.040
|View full text |Cite
|
Sign up to set email alerts
|

The approach of urologists to kidney stones in southeastern Anatolia: a questionnaire survey

Abstract: Objective: It is aimed to investigate the possible differences of urologist in the Southeastern Anatolia Region concerning kidney stone disease about treatment selections and processes. We also aimed to provide data to all institutions that perform educational activities in our country, including the Turkish Association of Urology and Endourology. Our study also sought to determine the treatment priorities in our region. Material and methods:A questionnaire consisting of 22 questions was prepared and delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
3

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
1
0
3
Order By: Relevance
“…The insidance of renal calculi can also change among different regions of Turkey according to ethiological reasons. 5 The rate of bladder calculi is also high among children in endemic countries, such as Turkey. A population based study of children in our country demonstrated that rate of bladder calculi is not as high as suspected.…”
Section: Discussionmentioning
confidence: 99%
“…The insidance of renal calculi can also change among different regions of Turkey according to ethiological reasons. 5 The rate of bladder calculi is also high among children in endemic countries, such as Turkey. A population based study of children in our country demonstrated that rate of bladder calculi is not as high as suspected.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Yüksek hava sıcaklıkları ve bunun yanında yeterli sıvı tüketilmemesi, hayvansal gıdalarla fazla beslenme, tuzlu yiyecekler nedeniyle Güneydoğu Anadolu Bölgesi'nde taş hastalığı, diğer bölgelerden daha sık görülmektedir . [2,6,8] Son 20 yıl içerisinde Marmara ve Ege Bölgesi'nde taş prevelansı hızla artmakta olup, sebep olarak Doğu ve Güneydoğu Anadolu Bölgesi'nden bu bölgelere fazla miktarda göç artışı gösterilmektedir. [14] Ülkemizde üriner sistem taş hastalığı insidansı yaşla artmakta olup, en sık 30-60'lı yaşlarda saptanmaktadır.…”
Section: Discussionunclassified
“…Güneydoğu Anadolu Bölgesi'nde taş hastalığı, yüksek hava sıcaklıkları, yeterli sıvı tüketilmemesi, hayvansal gıdalarla fazla beslenme, tuzlu yiyecekler nedeniyle diğer bölgelerden daha sık görülmektedir. [2,6,8] Taş hastalığının endemik olarak gözlendiği ülkemizde, hemen her türlü böbrek taşı tedavisi teknolojik ilerlemelere paralel olarak minimal invazif yöntemlerle (beden dışı şok dalga tedavisi, retrogratintrarenal cerrahi, perkütan nefrolitotomi ve laparoskopik taş cerrahisi) gerçekleştirilebilmektedir. Böbrek taşı cerrahisinde perkütan nefrolitotomi (PNL) altın standart yöntem olarak ülkemizde batıdan doğuya hemen her merkezde başarıyla uygulanmaktadır.…”
Section: Introductionunclassified
See 1 more Smart Citation